Competencies and Work Performance of School Paper Advisers in Public Schools - Anirica Dacumos (International Journal of Sustainable and Integrated Studies, 2026)
This study determined the extent of competencies and work performance of school paper advisers in selected upland schools in Tanay District, Division of Rizal, during School Year 2025–2026. It employed a descriptive survey research design and documentary analysis. The respondents were 54 school paper advisers and 163 campus journalists from 26 public schools. A researcher-made questionnaire checklist was used to assess the competencies of school paper advisers in terms of journalistic and teaching proficiency, mentorship and coaching, contextual intelligence and institutional navigation, and ethical and legal gatekeeping. Documentary analysis was conducted using the advisers’ Individual Performance Commitment and Review (IPCR) ratings as the basis for determining their level of work performance. Findings revealed that most school paper advisers were 31–40 years old, female, married, holders of master’s degrees, with more than 10 years of teaching experience, and had attended in-service trainings ranging from division to international levels. Most campus journalists were 14–16 years old, female, second- or third-born children, and belonged to average-income families. School paper advisers rated themselves as much competent, whereas campus journalists perceived them as moderately competent. A significant difference was found between the perceptions of the two groups regarding the advisers’ competencies across the identified dimensions. However, the personal attributes of both school paper advisers and campus journalists were not significantly associated with their perceptions of advisers’ competencies. The advisers demonstrated very satisfactory work performance based on their IPCR ratings, and a significant relationship was found between their perceived competencies and work performance. The study concluded that strengthening professional competencies may contribute to improved work performance among school paper advisers. It recommended the conduct of seminars, workshops, conferences, and specialized training in campus journalism, leadership, communication, ethics, and legal responsibilities, as well as the establishment of a professional network for school paper advisers. The proposed action plan was recommended for implementation, while parallel studies may be undertaken using additional variables and broader settings.